2023
DOI: 10.1049/icp.2023.0736
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of instrument transformers in power quality measurements: activities and results from 19NRM05 IT4PQ project

G. Crotti,
P. S. Letizia,
J. Meyer
et al.

Abstract: The accuracy of power quality measurements relies on the use of common measurement procedures and traceable measurement systems, which necessarily include instrument transformers. The paper provides an overview of the progress achieved within the EU project 19NRM05 IT4PQ in developing the needed metrological framework, in terms of performance indexes to qualify the instrument transformers for PQ measurements, simplified testing procedures and set-ups, and quantification of their behaviour under multiple influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…For the phase displacement, the voltage deviation is about 90 µrad at −25 °C and less than 40 µrad at 21 °C and 55 °C. These results are in agreement with similar work performed in the JRP IT4PQ [23]. The magnetic properties of the materials used to realize the voltage transformers change with thermal and mechanical treatment and with frequency, too.…”
Section: Influence Of Temperature On Accuracy At 50 Hzsupporting
confidence: 91%
See 1 more Smart Citation
“…For the phase displacement, the voltage deviation is about 90 µrad at −25 °C and less than 40 µrad at 21 °C and 55 °C. These results are in agreement with similar work performed in the JRP IT4PQ [23]. The magnetic properties of the materials used to realize the voltage transformers change with thermal and mechanical treatment and with frequency, too.…”
Section: Influence Of Temperature On Accuracy At 50 Hzsupporting
confidence: 91%
“…observed that the voltage deviation from 18 kV to 30 kV is more visible at low temperatures. For the ratio error, we observed a voltage deviation of about 275 ppm at −25 • C and less than 30 ppm at 21 • C and 55 • C. For the phase displacement, the voltage deviation is about 90 µrad at −25 • C and less than 40 µrad at 21 • C and 55 • C. These results are in agreement with similar work performed in the JRP IT4PQ[23].…”
supporting
confidence: 91%
“…Regarding the impact of the burden with different temperatures, it is observed that the impact of the VT burden decreases nonlinearly with a rising temperature. At a fundamental frequency, when comparing the ratio errors at the rated burden with respect to errors at no burden for different temperatures, it is found that the ratio error changes by 4.5% at −25 • C, by 2% at 20 • C, and by 1.5% at 55 • C. The same trend, with larger changes, occurs in the higher harmonics range [40].…”
Section: Temperature and Burdenmentioning
confidence: 80%
“…Similar observations were made when measuring the frequency response of the VT. However, at low temperatures, the deviations were more noticeable, regardless of the presence of vibration [31,40].…”
Section: Temperature and Vibrationmentioning
confidence: 89%
See 1 more Smart Citation